Proceedings of the Thirty-First International Joint Conference on Artificial Intelligence 2022
DOI: 10.24963/ijcai.2022/640
|View full text |Cite
|
Sign up to set email alerts
|

Shared Autonomy Systems with Stochastic Operator Models

Abstract: We consider the mobile robot path planning problem for a class of recurrent reachability objectives. These objectives are parameterized by the expected time needed to visit one position from another, the expected square of this time, and also the frequency of moves between two neighboring locations. We design an efficient strategy synthesis algorithm for recurrent reachability objectives and demonstrate its functionality on non-trivial instances.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 3 publications
0
5
0
Order By: Relevance
“…For example, past work has shown that when making decisions in groups, individuals adapt their own confidence estimates to align with others' [13], raising the possibility that metacognitive processes may be altered when collaborating with humans vs. machines. In addition, an illusion of confidence may play a role in collaborations involving delegation, where human operators can choose to delegate tasks to automated agents [38] and may choose to do so more often if higher confidence is attributed to a potential collaborator. The results of Experiment 5 are especially relevant in this respect, as they suggest that attributions of confidence affect advice taking in a scenario akin to AI support and assistance.…”
Section: Discussionmentioning
confidence: 99%
“…For example, past work has shown that when making decisions in groups, individuals adapt their own confidence estimates to align with others' [13], raising the possibility that metacognitive processes may be altered when collaborating with humans vs. machines. In addition, an illusion of confidence may play a role in collaborations involving delegation, where human operators can choose to delegate tasks to automated agents [38] and may choose to do so more often if higher confidence is attributed to a potential collaborator. The results of Experiment 5 are especially relevant in this respect, as they suggest that attributions of confidence affect advice taking in a scenario akin to AI support and assistance.…”
Section: Discussionmentioning
confidence: 99%
“…Changes to the autonomy level can occur at any time throughout a task or mission. These changes can be initiated by the robot (robot-initiative) ( Costen et al, 2022 ; Mahmud et al, 2023 ), the human supervisor (human-initiative), or from either the supervisor or the robot (mixed-initiative) ( Chiou et al, 2021 ). While our experiments and demonstration in this manuscript focus on a human-initiative system, robot competency assessment for autonomy adjustment can be applied to mixed-initiative and robot-initiative systems as well.…”
Section: Background and Related Workmentioning
confidence: 99%
“…Markov chains are established models for stochastic processes. Discrete-time Markov chains have been used to model environmental hazards (Tihanyi et al, 2021), resource constraints (de Nijs et al, 2018), disease spread (Gómez et al, 2010), and human task performance (Costen et al, 2022). However, many real world processes operate in continuous time.…”
Section: Modelling Stochastic Processes With Markov Chainsmentioning
confidence: 99%